(untitled) (The Journal of Psychology and Sociology, 2015)
Continuity of generations one of the most exciting social problems of our time, because it is the problem of the future of the world. In an era of rapid scientific and technological progress, the opening up of the Kazakhstan soci ety, the penetration of Western culture and the socalled «free democracy», as well as rapid physical and mental development of children today, in the minds of young people there is a change of the concept of family and marriage. Young people, often engaging in family and marriage relations, proclaims the «free love», implying that, the absence of any responsibility for each other, which is fraught with the destruction of the very concept of the family. Promo tion of samesex marriage under the aegis of democracy and freedom has a negative influence on the formation of family values in the society. Therefore, a large role in the promotion of family values among young people should belong to the older generation. Today, the strategic goal of family policy in the Republic of Kazakhstan is to strengthen the family institution, the develop ment of family life, ensure the growth of wealth, gender and birth rate. In the context of the transformation of Kazakh society and its integration into the world community of special importance the problem of preservation of spiri tual and moral values and family traditions, characteristics of family education.